Significance of the Energy Resources for Pakistan’s Economy: Challenges and the Way Forward - Rubab, Rahila Khatoon; Tagar, Hamzo Khan; Shoro, Iram; Jalbani, Muhammad Saleem (Archives of Business Research, 2022)
Energy has been widely demanded, due to increasing population pressure and changing consumptions pattern globally. Domestic and commercial activities have become more dependent on the energy sector in the 21st century. Reliable and affordable energy is the dream of developing countries for their economic growth and development because of its correlation to the subject matter. The rapid growth of the industries developed agriculture; modern trade and dynamic transportation facilities are mostly dependent on the energy sector. A decent supply of energy at a cheap rate for sustainable growth and development is the need of the hour in Pakistan. It is analyzed that the energy crisis began in the country in 1990, after Iraq and Kuwait war. Pakistan mostly depends on energy imports because energy resources of hydro powers, natural gas and oil fields are untapped due to a lack of sufficient investment and several other unavoidable circumstances. The basic aim and objectives of this study are to investigate and explore the major obstacles in efficient energy management to reduce the gap shortfall. This study recommends that the policymakers of the government of Pakistan specifically political economy managers focus attention and investment should be on green energy resources i.e., solar, wind energy, biogas and other options of alternatives energy resources in their policies and programs in the greater public interest of economic development for all in the region.